Students’ Sexual Identity Based on Interest, Style and Behavior - Neviyarni Neviyarni; Netrawati Netrawati; Riska Ahmad; Wiwi Delfita (Universitas Negeri Padang, 2020)
The right sexual identity, if a person is interested to the opposite sex. In fact, there are still some students who are known as homosexual. This article is aimed to define the sexual identity of students based on behavior, style and interest. This study utilized quantitative approach with descriptive type. The populations of the research were students of Universitas Negeri Padang 2017 and 2018 generation in amount of 15.752, and sample counted were 385 students (by using Taro Yamane formula and continued with Multistage Random Sampling Technique. The researcher employed instrument which isSexual Identity scale, model Gutman. After being analyzed with descriptive technique, the researcher got result that generally students tended to identify their sexual identity as heterosexual based on interest, behavior, and style. Counselor is hoped to be able to help students whom are identified as homosexual to the right direction(heterosexual) by giving counseling services needed by sexual identity.